ONLINE COURT PROCEEDINGS - H. Saidov (Scholar Express Journal, 2022)
This article examines online litigation, from registration to execution of a civl suit, its current status and the transparency of litigation.
Keywords: Online Court; Offline Court; Platform; Online Court Rules